IRRADIATION EFFECTS ON INSECTICIDES AS A POLLUTANT MODEL IN AQUEOUS SOLUTION - Hendig Winarno; Ermin Katrin Harantung (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2007)
Degradation of some insecticides i.e.: fenitrothion, prothiofos, and cypermetrin as a model pollutant was carried out using gamma irradiation of 60Co. Irradiation-induced of fenitrothion in solution acid medium gave the significant effect on the decrease of its concentration. The optimum condition for degradation of fenitrothion (55.5 mg/L) was irradiation at 6 kGy with aeration in initial pH 5.6. At this condition, the concentration of fenitrothion decreased up to 97%. Determination of organic acids in irradiated product by HPLC method showed that oxalic acid and formic acid were clarified as organic acid-degraded products of fenitrothion with the concentration of 23.0 mg/L and 2.5 mg/L respectively. The irradiation of prothiofos in aqueous solution (50 mg/L), showed that irradiation at a dose of 8 kGy and initial pH 7 gave the optimum degradation. At this condition, the concentration of prothiofos decreased up to 98%. Determination of irradiated product by HPLC method showed that oxalic acid (18 mg/L) was clarified as organic acid-degraded product of prothiofos. In the case of cypermetrin, the optimum condition for its degradation was irradiation with aeration of cypermetrin (40 mg/L) at a dose of 20 kGy, initial pH 11, and adding the catalyst 0.05% of FeCl3. At that condition, cypermetrin decreased up to 87% and COD of solution decreased up to 78%. The organic acid detected at optimum condition as degradation products were oxalic acid (1.1 g/L), maleic acid (9.0 g/L), formic acid (127.0 g/L), and acetic acid (286.0 g/L). From these results, it could be concluded that ionizing radiation can be used as a tool to degrade insecticides as organic pollutants.